Making meaning in museum exhibitions: design, agency and (re-)representation - Sophia Diamantopoulou; Eva Insulander; Fredrik Lindstrand (Stockholm University Press, 2012)
Based on a three year project 'The Museum, the Exhibition and the Visitors: Meaning making in a new arena for learning and communication' (funded by the Swedish Research Council) the article asks what might be constants of meaning-making as visitors engage in a Museum exhibition.